Chronotop in the Aspect of Semiotics - Temirbolat, Alua B. (Respectus Philologicus, 2005)
The article is dedicated to researching the problem of artistic chronotop, which is one of the most topical in modern philological science. The given category is comprehended from the point of view of semiotics.The semantic field of category time-space, the structure of category time-space, and its role in a literary work are exposed to the analysis. Great emphasis is laid on studying the interrelation of chronotop with other levels of the artistic text and its features as a communicative system. The article investigates the specificity of the interaction between the author, reader, and literary character’s individual times and spaces.